Merleau-Ponty's Conception of Dialectics in Phenomenology of Perception. Issue 3 (14th October 2016) - Pollard, Christopher
Abstract : Although the fact that Merleau-Ponty has a dialectical approach in Phenomenology of Perception has been discussed in recent Anglophone readings, there has not been an explicit clarification as to how his varying usages of the term hang together. Given his repeated references to Hegel and to dialectics, coupled with the fact that dialectics are not part of the Husserlian phenomenology or Heideggerean existentialism from which Merleau-Ponty draws so much, the question of just what he does with the idea of dialectics presents itself. In this paper I argue that, in Phenomenology of Perception, Merleau-Ponty saw Hegel as providing a model for the conception of rationality and meaning that must underpin the existentialist response to the problems bequeathed him by Husserlian phenomenology: namely, the problems of embodiment, perception and the constitution of the world. In connection with this, I suggest an interpretation of Merleau-Ponty's "existential dialectics" that focuses on his three principal uses of the term: 1) a "dialectic of objective thought, " 2) a set of existential-dialectical categories intended to capture the ontological structure of the "body-subject" as "being-in-the-world, " and 3) a dialectic at the cultural level concerning others and history.